1977
DOI: 10.1139/f77-134
|View full text |Cite
|
Sign up to set email alerts
|

Extent of Effluent Influence on Lake Water Determined by Bacterial Population Distributions

Abstract: Populations of heterotrophic bacteria, total and fecal coliforms, and sulfur cycle bacteria were measured in a large body of water receiving the effluent of a pulp and paper industry. Elevated bacterial populations were detected near the effluent outfall but persistent populations, larger than those in unaffected lake water, extended as far as 19 km from the effluent outfall. This ability to detect influences to distances up to 19 km adds a new dimension to a description of a mixing zone receiving industrial e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1981
1981
1996
1996

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Heterotrophic activity was chosen as the main parameter to be measured because heterotrophic bacteria are mainly responsible for the decomposition of organic matter and are thus the major cause of oxygen depletion in the water . Rao et al (1976) and Rokosh et al (1977) found aerobic heterotrophic bacteria to be the most sensitive indicators of the effects of effluents . If the numbers of aerobic heterotrophs can indicate these effects it would seem reasonable that their metabolic activity should also do so .…”
Section: Introductionmentioning
confidence: 99%
“…Heterotrophic activity was chosen as the main parameter to be measured because heterotrophic bacteria are mainly responsible for the decomposition of organic matter and are thus the major cause of oxygen depletion in the water . Rao et al (1976) and Rokosh et al (1977) found aerobic heterotrophic bacteria to be the most sensitive indicators of the effects of effluents . If the numbers of aerobic heterotrophs can indicate these effects it would seem reasonable that their metabolic activity should also do so .…”
Section: Introductionmentioning
confidence: 99%